2020
DOI: 10.1186/s12889-020-09448-0
|View full text |Cite
|
Sign up to set email alerts
|

Internet use and need for digital health technology among the elderly: a cross-sectional survey in China

Abstract: Background China is becoming an aging society at the fastest pace in history, and there are a large number of empty nesters in the country. With economic and social development, internal support systems among families are gradually weakening. Supporting the elderly is thus emerging as a significant issue, and promoting digital health technologies is an effective way to help address it. Encouraging the application of Internet to elderly care and Internet use among the elderly are important means of promoting di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 32 publications
4
73
0
1
Order By: Relevance
“…Health codes require smartphones and Internet connections. However, the most recent report shows that getting around in China without a smartphone or being off-line is still a difficult task in 2020 [ 38 , 39 ], and this has been a particular problem for the country’s elderly population [ 40 ], especially when they travel by public transportation without health codes during the pandemic. Consequently, the general public has tried to speak on behalf of elderly travelers on social media.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health codes require smartphones and Internet connections. However, the most recent report shows that getting around in China without a smartphone or being off-line is still a difficult task in 2020 [ 38 , 39 ], and this has been a particular problem for the country’s elderly population [ 40 ], especially when they travel by public transportation without health codes during the pandemic. Consequently, the general public has tried to speak on behalf of elderly travelers on social media.…”
Section: Resultsmentioning
confidence: 99%
“…Elderly people were more likely to learn and use smartphones and the Internet with support from others. Therefore, society, governments, and transportation service providers should work together to help elderly people reap the benefits of the Internet in future situations and eventually improve the equity and fairness of public policies [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other forms of internet-based services, IBMS are relatively new, with technological content for the elderly. On the one hand, when older adults access these applications, internet medical services can: (i) solve practical problems related to health management and reduce the burden on caregivers; (ii) enhance their learning ability and confidence [8,31]; (iii) alleviate their social alienation and anxiety, while improving their self-efficacy, sense of control, and life satisfaction. On the other hand, as with other internet-based services, older people often lack confidence in their learning ability and even refuse to accept new knowledge, and the main reasons for this include a lack of technical support and poor understanding about the parameters, functions, and payment.…”
Section: Internet Use and The Pursuit Of Well-being By Older Adultsmentioning
confidence: 99%
“…Notably, the popularity of internet technology and convenient network tools has increased over the last 20 years. During this process, the "new generation" of older people have preliminarily mastered some basic network skills through various auxiliary supports such as connecting to the Internet, searching for information, and downloading and installing mobile phone applications [8,9]. Especially with the growing popularity of smart phones, receiving information, entertainment, and other internet-based services have gradually become a part of the lives of the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that personal status, including gender, age, education and physical health, is associated with the need for digital health technology among disabled older adults. [19][20][21] Disabled older adults who are female, [22][23][24] have greater education [23][24][25] and physical conditions [26][27][28] are more likely to use the internet. It is more difficult to use the internet for disabled older adults who are suffering from physical and functional disabilities.…”
Section: Introductionmentioning
confidence: 99%